Magnetic tagging of cell-derived microparticles: new prospects for imaging and manipulation of these mediators of biological information. (July 2010) - Vats, Nidhi; Wilhelm, Claire; Rautou, Pierre-Emmanuel; Poirier-Quinot, Marie; Péchoux, Christine; Devue, Cécile; Boulanger, Chantal M; Gazeau, Florence
Aims: Submicron membrane fragments termed microparticles (MPs), which are released by apoptotic or activated cells, are newly considered as vectors of biological information and actors of pathology development. We propose the tagging of MPs with magnetic nanoparticles as a new approach allowing imaging, manipulation and targeting of cell-derived MPs.Materials & methods: MPs generated in vitro from human endothelial cells or isolated from atherosclerotic plaques were labeled using citrate-coated 8 nm iron-oxide nanoparticles. MPs were tagged with magnetic nanoparticles on their surface and detected as Annexin-V positive by flow cytometry.Results: Labeled MPs could be mobilized, isolated and manipulated at a distance in a magnetic field gradient. Magnetic mobility of labeled MPs was quantified by micromagnetophoresis. Interactions of labeled MPs with endothelial cells could be triggered and modulated by magnetic guidance. Nanoparticles served as tracers at different scales: at the subcellular level by electron microscopy, at the cellular level by histology and at the macroscopic level by MRI.Conclusion: Magnetic labeling of biogenic MPs opens new prospects for noninvasive monitoring and distal manipulations of these biological effectors.